2007
DOI: 10.1080/14786430701654378
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the B2 phase in Ti–25Al–25Mo alloy

Abstract: The structure of the B2 phase has been investigated in Ti-25Al-25Mo alloy using Rietveld refinement of X-ray and neutron diffraction data in as-cast and solution-treated conditions. Different initial structure models have been used for the refinement. The site occupancy of the various chemical constituents in the B2 phase has been calculated and compared with earlier investigations. The relative merits of neutron diffraction over X-ray diffraction for structural refinement of the B2 phase in Ti-25Al-25Mo alloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The small amount of M atoms can also occupy on A sites either due to excess from B sites or antisite effect in non-stoichiometric alloys. The results obtained by Singh et al [5] and Banerjee et al [12] are such examples. In case of alloys containing Ti !50 atom%, the A sites are occupied by Ti atoms while the B sites are occupied by Al and M atoms.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The small amount of M atoms can also occupy on A sites either due to excess from B sites or antisite effect in non-stoichiometric alloys. The results obtained by Singh et al [5] and Banerjee et al [12] are such examples. In case of alloys containing Ti !50 atom%, the A sites are occupied by Ti atoms while the B sites are occupied by Al and M atoms.…”
Section: Resultsmentioning
confidence: 84%
“…The B2 phase contains two distinct sublattices A and B, which are located at the cell corners (0, 0, 0) and at body-centered positions (1/2, 1/2, 1/2). The site occupancy of the B2 has been studied by several investigators using X-ray and neutron diffraction techniques [5,9,[11][12][13][14]. These results can be classified into two groups: (1) The alloys containing titanium 50 atom% and (2) the alloys containing Ti !50 atom%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alloy was found to contain the b 0 phase, and Rietveld refinement of the data showed that Ti atoms occupy A sites and Al and Mo atoms occupy the B sites in the CsCl structure. Excess Mo atoms can also occupy A sites with Ti atoms [59].…”
Section: Phase Relations In the Tiealemo Systemmentioning
confidence: 99%
“…However, Morris et al [3] claimed to also have the a 2 -Ti 3 Al phase at 1473 K. The ordered b 0 phase was first determined by Böhm and Löh-berg [58] in alloys within the composition range from z60 wt.%Mo to z30 wt.%Mo at 50 at.%Ti which were heat treated at 1073 K and then quenched. Singh et al [59] performed Rietveld refinement of X-ray and neutron diffraction data from an alloy of composition 50 at.%Tie25 at.%Ale25 at.%Mo which was homogenized at 1273 K and furnace cooled. The alloy was found to contain the b 0 phase, and Rietveld refinement of the data showed that Ti atoms occupy A sites and Al and Mo atoms occupy the B sites in the CsCl structure.…”
Section: Phase Relations In the Tiealemo Systemmentioning
confidence: 99%